Balance of Payment Statistics Yearbook 2018. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2018)
This paper analyzes In the World and Regional Tables, missing data are estimated for countries by IMF staff to the extent possible. The estimation procedure is based largely on the use of the World Economic Outlook (WEO) database in BPM6 format. The BPM6-based WEO provides expanded data coverage for some series and facilitates an improved basis for estimation procedures used in BOPSY. However, data published in BOPSY may differ from balance-of-payments data published in the WEO mainly due to timing and estimation methodology differences. The following outlines the methodology used to gap-fill balance-of-payments data where country data are missing. For goods and services transactions, where data gaps exist in years prior to estimates are made by applying the growth rates derived from the WEO for the missing year(s) to the latest reported annual data (debits and credits). In cases where there are gaps for the entire period, WEO data are inserted directly.